2003
DOI: 10.1016/s0005-2736(02)00683-1
|View full text |Cite
|
Sign up to set email alerts
|

No entry for TAT(44–57) into liposomes and intact MDCK cells: novel approach to study membrane permeation of cell-penetrating peptides

Abstract: Cell penetrating peptides (CPPs) have been postulated to carry macromolecules across cell plasma membranes without the need of receptors, transporters, endocytosis or any energy-consuming mechanism. We developed an assay to study lipid bilayer permeation of CPPs. HIV-1 TAT peptides were conjugated to N-(4-carboxy-3-hydroxyphenyl)maleimide (SAM) and incubated with Tb(3+)-containing liposomes. Upon chelation of Tb(3+) by an aromatic carboxylic acid, the fluorescence of Tb(3+) increases many fold. The CPP TAT(44-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
85
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 24 publications
7
85
6
Order By: Relevance
“…Quantitative analysis of SecPen transfer from ten independent experiments indicates that, following the addition of 10 nmol of peptide in the basolateral compartment, 3.3 Ϯ 0.7 pmol of peptide are retrieved in the apical compartment after 1 h. In similar conditions, the transcytosis of transferrin is 50-fold less efficient. Previous studies on the passage of PTDs across epithelial monolayers have demonstrated that Tat and Penetratin PTDs are incapable of transcellular transport (13)(14)(15)(16) and, moreover, are poorly internalized by confluent MDCK cells (13,14,16). In agreement with these observations, we found that neither of these two peptides is transported across the epithelium in our system and that Penetratin internalization is significantly reduced when MDCK cells reach confluence (not shown).…”
Section: Discussionsupporting
confidence: 90%
“…Quantitative analysis of SecPen transfer from ten independent experiments indicates that, following the addition of 10 nmol of peptide in the basolateral compartment, 3.3 Ϯ 0.7 pmol of peptide are retrieved in the apical compartment after 1 h. In similar conditions, the transcytosis of transferrin is 50-fold less efficient. Previous studies on the passage of PTDs across epithelial monolayers have demonstrated that Tat and Penetratin PTDs are incapable of transcellular transport (13)(14)(15)(16) and, moreover, are poorly internalized by confluent MDCK cells (13,14,16). In agreement with these observations, we found that neither of these two peptides is transported across the epithelium in our system and that Penetratin internalization is significantly reduced when MDCK cells reach confluence (not shown).…”
Section: Discussionsupporting
confidence: 90%
“…For about a decade, it was commonly accepted that, despite their highly polar nature, PTDs are able to rapidly and efficiently translocate directly through the lipid bilayer, thus delivering their cargo into the cytoplasm and nucleus in a receptor-and energy-independent way (14,15). This model was supported by a large number of indirect evidence including temperature, ATP, and receptor independence of cellular uptake (11)(12)(13)(14), but attempts to directly validate this model on protein-free lipid bilayer systems gave contradictory results (31,32). Moreover, it was recently shown that apparent ATP and temperature independence and fast kinetics of PTD uptake result from artifacts of cell fixation and incomplete removal of surface-bound peptide (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…This energy-independent internalization property of ZEBRA-MD-EGFP is highly favorable because endosomal trapping can be circumvented, which seems to be the major bottleneck for most CPP, as, for example, TAT, which enters cell by macropinocytosis (15) and fails to enter into liposomes (43,49). Further study to determine the amino acids from the MD responsible for the translocation properties will permit a better understanding of the molecular mechanism of ZEBRA cellular uptake.…”
Section: Discussionmentioning
confidence: 99%